Cytogenetics of I-san fighting fish (Betta smaragdina Ladiges, 1972) - เครือเนตร วิไลลักษณ์; นิธิกุลวรวงศ์ ณัฎฐา (KKU Science Journal, 2013)
The first Cytogenetics of I-san fighting fish (Betta smaragdina Ladiges, 1972) at Phuhinladchorfar canal, Nong Bua Lam Phu province was investigated in this study. Mitotic chromosome was prepared directly from kidney of specimens after In vivo colchicines treatment. The metaphase spreads were performed on microscopic slides and air-dried. Conventional staining technique was applied to stain the chromosome with Giemsa’s solution 20%. The results showed that the number of diploid chromosome of I-san fighting fish was 2n = 42, fundamental number (NF) was 50 in both male and female. The types of chromosomes were 6 large acrocentric, 4 large telocentric, 2 medium acrocentric, 20 medium telocentric and 10 small telocentric chromosomes. The karyotypes are not different between sex chromosomes male and female. The karyotype formula for the I-san fighting fish is as follow : 2n (42) = L6a + L4t + M2a + M20t + S10t